Perancangan dan Implementasi Robot Beroda Kendali Jarak Jauh sebagai Alat Uji Kualitas Jaringan WLAN Berbasis Raspberry Pi 3 - Asril Rahmat Prakoso; Sandy Putra Dharma Pratama; Riza Agung Firmansyah; Wahyu Setyo Pambudi; Yuliyanto Agung Prabowo; Syahri Muharom (SMARTICS Journal, 2025)
Wireless LAN (WLAN) network quality in indoor environments is significantly affected by distance, building conditions, and physical obstacles such as concrete walls, glass, and other materials. Manually testing WiFi signal quality at multiple points is repetitive, time-consuming, and potentially leads to data inconsistencies. Therefore, this research aims to design and build a WiFi service coverage area testing system using a Raspberry Pi 3-based remote-controlled wheeled robot as a more efficient and controlled measurement alternative. The robot functions as a mobile platform that acts as a WiFi client to measure Received Signal Strength Indicator (RSSI) values ​​at various coordinate points in the test environment. The system was developed using a Raspberry Pi 3 as the control center, Python programming for the control system and RSSI reading using the PyWiFi library, and OpenCV for real-time camera display. The robot is controlled via a remote interface and moves according to a predetermined coordinate scheme. Tests were conducted at 35 measurement points, comparing the RSSI results from the robot prototype with the WiFi Analyzer application on an Android device. The test results show that RSSI variations are influenced by the distance from the access point and the physical environmental conditions. Data comparison shows an average error percentage of 5.51%, which indicates a system success rate of 94.49%.